PENGEMBANGAN MEDIA GAME INTERAKTIF ELEKTRONIK BERBASIS QUIZWHIZZER PADA SUBTEMA USAHA PELESTARIAN LINGKUNGAN - Lia Audina; Teti Rostikawati; Resyi A. Gani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the development and feasibility testing of QuizWhizzer-based Electronic Interactive Game media with the Sub-theme of An Attempt for Environmental Conservation at the fifthgrade students of SDN Cikutamahi 01. The method used is the Research and Development (R&D) with the ADDIE method (Analyzing, Designing, Developing, Implementing, and Evaluating). To find out the feasibility of QuizWhizzer-based Electronic Interactive game media, the researchers provided validation for 6 experts, trials, and field trials. The results indicate that the QuizWhizzer-based Electronic Interactive Game is feasible to use as an evaluation in the classroom. Based on the data validation, the media expert validation average percentage was 92%, the linguist validation average percentage was 100%, and the material expert validation average percentage was 98.33%. In addition, the results of the small group trial obtained 81.33%, and the data from the field trial obtained 95.23% in the "Very Good" category. It means that the electronic interactive game media based on QuizWhizzer on the subtheme of environmental conservation that was developed is very feasible to use as an evaluation for students at class V of SDN Cikutamahi 01.